2015
DOI: 10.1515/amm-2015-0256
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Of Multi-Module CrN/CrCN Coatings

Abstract: In the paper was proposed optimization procedure supporting the prototyping of the geometry of multi-module CrN /CrCN coatings, deposited on substrates from 42CrMo4 steel, in respect of mechanical properties. Adopted decision criteria were the functions of the state of internal stress and strain in the coating and substrate, caused by external mechanical loads. Using developed optimization procedure the set of optimal solutions (Pareto-optimal solutions) of coatings geometry parameters, due to the adopted deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…For monolayer coatings deposited by PVD techniques, it is often observed that increasing the hardness of the coatings is accompanied by a simultaneous increase in the Young's modulus and decrease of their ductility (impact resistance), which leads to a reduction of coating's fracture toughness due to the reduction of their ability to dissipate mechanical energy (through plastic deformation). In order to limit these effects, for example, a more complex structure of the coating is used such as multilayer coatings and multi-module Cr/CrN (Marulanda et al, 2012;Polcar et al, 2009;Ratajski et al, 2015), CrN/CrCN (Gilewicz et al, 2015;Szparaga et al, 2015aSzparaga et al, , 2015b or gradient CrN/Cr(C)N coatings (Fuentesa et al, 2008;Ratajski and Szparaga, 2012;Szparaga et al, 2015c;Zhang et al, 2009). The such structure of coating increases the resistance to cracking and enhances the adhesion state, e.g., by reducing residual stresses in the coating.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For monolayer coatings deposited by PVD techniques, it is often observed that increasing the hardness of the coatings is accompanied by a simultaneous increase in the Young's modulus and decrease of their ductility (impact resistance), which leads to a reduction of coating's fracture toughness due to the reduction of their ability to dissipate mechanical energy (through plastic deformation). In order to limit these effects, for example, a more complex structure of the coating is used such as multilayer coatings and multi-module Cr/CrN (Marulanda et al, 2012;Polcar et al, 2009;Ratajski et al, 2015), CrN/CrCN (Gilewicz et al, 2015;Szparaga et al, 2015aSzparaga et al, , 2015b or gradient CrN/Cr(C)N coatings (Fuentesa et al, 2008;Ratajski and Szparaga, 2012;Szparaga et al, 2015c;Zhang et al, 2009). The such structure of coating increases the resistance to cracking and enhances the adhesion state, e.g., by reducing residual stresses in the coating.…”
Section: Introductionmentioning
confidence: 99%
“…For nearly three decades in designing of structure of multi-layer, monolayer and multi-module coatings a great role play finite element method (FEM) simulations (Dobrzański et al, 2007;Pakuła et al, 2016;Ratajski and Szparaga, 2012;Szparaga et al, 2015aSzparaga et al, , 2015cŚliwa et al, 2016;Śliwa, 2017;Zukowska et al, 2016). Among other FEM model was used in optimisation procedure for eight-layer Cr/CrN coating on A2 steel substrate in terms of mechanical properties (Lakkaraju et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finite elements method is at present one of most widely used practical methods of solving of various engineering problems and it permits on time shortening of projecting and gives possibility to research the influence of each factors in the mathematical model [1][2][3][4][5][6]. Usage of this method from economic point of view is well-founded because more than once it permits to avoid expensive laboratory investigations, and results obtained during simulation are reliable and approximate to real values [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Keywords:, Computational materials science; Finite Element Method, Stress, Strain, Deformation, Anatomical surgical tweezers A contemporary technological development makes it necessary to look for new constructional solutions that aim at the improvement of the effectiveness and quality of a product, at the minimization of dimension and mass as well as the increasing of reliability and dimension stability in the operation conditions [1][2][3][4][5][6]. Tweezers are classified as picking tools consisting of two arms produced in a plastic working process and connected permanently by welding.…”
mentioning
confidence: 99%